Palliative care in progressive multiple sclerosis. (1st February 2017) - D'Amico, Emanuele; Zanghì, Aurora; Patti, Francesco; Zappia, Mario
ABSTRACT: Introduction : Multiple sclerosis (MS) is a progressive disease of the central nervous system with unknown etiology. It could be associated with severe disability and losses of physical, psychological and social role functioning over time. People with MS share experiences in common with people affected by diseases with a shorter and clearer terminal phase. Therefore, it is appropriate to offer a palliative care approach to people with severe MS and their caregivers. Areas covered : Benefits for severe MS patients and their caregivers were shown when palliative care was included in their care. However, many neurologists show no interest toward palliative care services for people with severe MS. Misunderstandings about the services of palliative care are still prevalent. Expert commentary : When all results are considered, they show that palliative care for severe MS patients may be beneficial. The five-year view will discuss the barriers of palliative care inclusion for people with severe MS.